2022
DOI: 10.3389/fgene.2022.824483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Co-Existing Mutations and Gene Expression Trends Associated With K13-Mediated Artemisinin Resistance in Plasmodium falciparum

Abstract: Plasmodium falciparum infects millions and kills thousands of people annually the world over. With the emergence of artemisinin and/or multidrug resistant strains of the pathogen, it has become even more challenging to control and eliminate the disease. Multiomics studies of the parasite have started to provide a glimpse into the confounding genetics and mechanisms of artemisinin resistance and identified mutations in Kelch13 (K13) as a molecular marker of resistance. Over the years, thousands of genomes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…protein-protein interactions between P. falciparum and the red blood cell). Upregulation of exported proteins has been previously observed in both the artemisinin resistance transcriptome and as a response to nutrient limitation 3638 . Translational regulation was also significantly upregulated in all three conditions in concordance with previous knowledge of the eIF2α-mediated response under nutrient stress ( Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…protein-protein interactions between P. falciparum and the red blood cell). Upregulation of exported proteins has been previously observed in both the artemisinin resistance transcriptome and as a response to nutrient limitation 3638 . Translational regulation was also significantly upregulated in all three conditions in concordance with previous knowledge of the eIF2α-mediated response under nutrient stress ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…C ) Previous studies identified pathways associated with artemisinin tolerance. Vesicular trafficking: kelch13 28 , coronon 39 , Ap2μ 59 ; Autophagy: ATG18 29,31 ; Translational regulation: unfolded protein response 60 , proteasomal degradation (UBP1 59 ); Exported proteins 36,38 ; Invasion: GLURP and Phil1 40 ; Kinome: STK2, STK, CDPK 40 , Latency: grey text-unclear if distinct from nutrient-dependent latency or directly contributes to tolerance 25,61 .…”
Section: Discussionmentioning
confidence: 99%
“…To identify genes with high polymorphism in Indian isolates specifically, we conducted an analysis of single nucleotide polymorphisms (SNPs) to identify genes exhibiting high polymorphism. We partitioned the SNP dataset to identify mutations present in more than 75% of Indian isolates and less than 25% of other global isolates (adapted from a previous study by ( Rawat et al, 2022 )). From this analysis, we identified 1581 mutations that were specific to Indian isolates, spread across 922 genes ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates a possibility of PfKelch13 independent artemisinin resistance by a novel set of mutations. Since there are ample reports suggesting ACT resistance independent of PfKelch13 ( Das et al, 2021 ; Ghanchi et al, 2021 ; Nima et al, 2022 ), we looked into a list of mutations of genes that have a high association probability in ACT resistant samples ( Rawat et al, 2022 ). We then compared the list of genes having mutations in Indian isolates with that of genes defined to be co-existing in PfKelch13 mutated/artemisinin resistance isolates ( Rawat et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation